Utilización del hongo Pleurotus sapidus. en la degradación lignocelulósica del rastrojo de maíz, para la elaboración de abono en agricultura orgánica - Mendieta Morrillo, Ronald Roberty (2013)
Research´s general objective was to apply the mushroom “Pleurotus sapidus” in a corn stover to accelerate the degradation lignocellulosic to obtain organic fertilizer. According to the specific objectives we have; to determinate the best way of cultivation for the reproduction of in vitro P. sapidus, at the microbiology laboratory, To demonstrate the efficiency of the mushroom P. sapidus, during the degradation process of the organic material ; to realize an economic analysis of the best treatment to obtain information of feasibility. The experiment number one was made under a ( DCA) unifactorial 3 ( types of means) with five repetitions where the best means of cultivation for the reproduction In vitro of the mushroom P. sapidus was the cultivation means “Sabouraud” by this way we obtained 88.86 mm of average diameter and the best type of mycelial morphology (cottony lush ) The experiment number two was done by a ( DCA) with three treatment and five repetitions, each repetition was formed by kg of substratum where the best concentration of mushroom´s seed for the degradation and production of ”mushrooms” was the 0.06 kg/kg of substratum obtaining 12.05 of lignin´s degradation. The most decrease of the percentage of relation with C:N, was presented with efficiency 88.98 % less according to the percentage of the initial mass and the best alternative of biotechnology production to manifest a low price per Kl of product 0.45 y 5.20 dollars. The best percentage of mineralized nutrients was obtained by the treatment number one with (NPK) presenting values of 0.76, 0.24 y 0.53%.